Pemberdayaan Ekonomi Nelayan melalui Pembuatan Abon Ikan Cakalang untuk Pengentasan Kemiskinan Ekstrem di Desa Patoameme Kecamatan Botumoito Kabupaten Boalemo - Djalil, Mukhlisnah; Muhamad, Abdurahman Kano; J. Lapalao, Sintiani (LP2M IAIN Sultan Amai Gorontalo, 2025)
Efforts to empower the economy of fishermen through the development of fisheries-based businesses are very necessary to increase family income and reduce extreme poverty. The purpose of this community service activity is to increase the income of fishermen's families through diversification of fisheries-based businesses. Creating a sustainable program that focuses on improving the economic welfare and health of fishermen's families. The training method in the core program is through a participatory approach. The implementing team has carried out community service activities, in a series of 2024 student KKN-PAR programs according to the stages of the plan and the resulting achievement targets. The results of the implementation of community service are based on the realization related to the achievement targets, namely the eradication of extreme poverty. Through the Empowerment of Small, Micro and Medium Enterprises, the core program of KKN-PAR UNUGO makes SKIPJACK TUNA FLOS, which later this activity will have an impact on improving the quality of human resources in the Patoameme village community.